Peculiarities of injuries in Syrian athletes aged 15-17 - Mai, A.; Sobyanin, F. I.; Kolesnikov, N. V.; Chukanova, E. K. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the features of injuries in Syrian athletes of different sexes at the age of 15-17 years. Methods and structure of the study. A complex of research methods was used, including the analysis of scientific and methodological literature, interviews with athletes of different sexes, and a questionnaire survey. During mathematical and statistical processing of data, the reliability of differences in the number of injuries between boys and girls aged 15-17 was determined with calculations using the criterion. The calculations were aimed at identifying differences between athletes of different sexes separately for each type of injury and then for all types of injuries. Then the causes of injuries were determined using the example of the ankle joint in athletes and their percentage. The empirical part of the study was organized in Syria during the competitions for the Cup of the Republic in athletics. Results and conclusions. For most types of injuries between Syrian boys and girls aged 15-17 years old involved in athletics, no significant differences were found. An exception is a significant difference between boys and girls in getting tendon ruptures, which was found only in girls: the empirical chi-square value of 5 turned out to be greater than its tabular value (3.84) at a significance level of 0.05. The most common injuries among athletes involved in athletics were muscle cramps, muscle tears and sprains. The main causes of injuries in the example of the ankle joint in Syrian athletes are insufficient warm-up, overtraining, lack of consideration for the individual characteristics of the athlete, insufficient recovery, unsuitability of places for training. The data obtained can be taken into account in the training of young athletes aged 15-17 years.